First pollen survey of murundus in the Chapada Diamantina region of the state of Bahia, Brazil - Oliveira,Paulino Pereira (2014)
This was a pollen survey, in which we analyzed the sediments and moss polsters of murundus (termite mounds) in the Chapada Diamantina region of the state of Bahia, Brazil. Palynological treatment revealed the presence of 53 pollen types in murundus sediments, of which 23 were related to plants in the semi-arid zone and 30 remained unidentified. In moss polster samples, the pollen assemblage comprised 42 pollen types for which taxonomic affinities were identified and 54 for which they were not. In our comparison of the two pollen assemblages, we found that moss polsters and murundu sediments shared 15 pollen types. For some of the pollen grains in the murundus sediments, it was not possible to make reliable interpretations because of small number of grains and the poor state of conservation. In contrast, the pollen analyses of the moss polster samples showed that they could represent a useful tool for studies of pollen rain. To our knowledge, this is the first study of murundus as natural pollen collectors. Our findings suggest new possibilities for the use of the pollen records preserved in termite mounds.